2010
DOI: 10.1016/j.molcel.2009.12.034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ABCE1 in Eukaryotic Posttermination Ribosomal Recycling

Abstract: After termination, eukaryotic 80S ribosomes remain associated with mRNA, P-site deacylated tRNA and release factor eRF1, and must be recycled by dissociating these ligands and separating ribosomes into subunits. Although recycling of eukaryotic post-termination complexes (post-TCs) can be mediated by initiation factors eIF3, eIF1 and eIF1A (Pisarev et al., 2007), this energy-free mechanism can function only in a narrow range of low Mg2+ concentrations. Here we report that ABCE1, a conserved and essential membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
389
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(405 citation statements)
references
References 32 publications
(63 reference statements)
15
389
1
Order By: Relevance
“…The same study demonstrated that downregulation of ABCE1 protein leads to defects in the recognition of a stop codon. By contrast, ABCE1 protein was identified to strongly enhance ribosome recycling (34). After translation termination and release of polypeptide chain catalyzed by aRF1, ABCE1 protein docks to stop codon programmed ribosome via aRF1 positioned at A-site, ATP binding to ABCE1 protein induces a conformational change into its closed state, which reorganizes the FeS cluster domain to drive ribosome splitting and release of aRF1.…”
Section: Abce1 Protein Relates Closely With Eukaryotic Translationmentioning
confidence: 99%
“…The same study demonstrated that downregulation of ABCE1 protein leads to defects in the recognition of a stop codon. By contrast, ABCE1 protein was identified to strongly enhance ribosome recycling (34). After translation termination and release of polypeptide chain catalyzed by aRF1, ABCE1 protein docks to stop codon programmed ribosome via aRF1 positioned at A-site, ATP binding to ABCE1 protein induces a conformational change into its closed state, which reorganizes the FeS cluster domain to drive ribosome splitting and release of aRF1.…”
Section: Abce1 Protein Relates Closely With Eukaryotic Translationmentioning
confidence: 99%
“…Some differing data exist with respect to the necessity of ATP binding versus ATP hydrolysis in this splitting reaction. While in one study on the archaeal system a non-hydrolysable ATP analog triggered splitting (Barthelme et al , 2011 ), in two other studies on the eukaryotic and archaeal systems, hydrolysis competent ATP was necessary (Pisarev et al , 2010 ;Becker et al , 2012 ). However, the stability of ribosomes is sensitive to buffer conditions (especially magnesium), which may account for these discrepancies.…”
Section: Asymmetry and Allosteric Regulation: A New Chapter In Abc Prmentioning
confidence: 99%
“…Unexpectedly, work from the Krebber and Ficner labs found that ABCE1 physically interacts with eRF1 and is required for proper stop codon recognition (Khoshnevis et al , 2010 ). At the same time the Pestova lab showed that ABCE1 functions in mammalian ribosome recycling by studying ABCE1 promoted ribosome splitting in biochemical assays (Pisarev et al , 2010 ). Here, Pestova and colleagues found that the ATPase activity of ABCE1 is stimulated by post-termination complexes and that ABCE1 splits ribosomes using ATP hydrolysis (Pisarev et al , 2010 ).…”
Section: Abce1 Is a Eukaryotic And Archaeal Termination And Ribosome-mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Besides promoting translation termination, ABCE1 can act as an efficient ribosome recycling factor catalyzing post-termination complex dissociation at various conditions. 22 In addition to canonical termination, ABCE1 dissociates stalled and vacant ribosomes acting in quality control mechanisms during mRNA translation and ribosome biogenesis, and in regulation of available ribosome pool. [23][24][25] Moreover, ABCE1 recycling activity may control non-canonical 3 0 -UTR translation on stalled ribosomes during stress.…”
Section: Introductionmentioning
confidence: 99%